DETERMINANTS OF E-COMMERCE USER SATISFACTION: THE MEDIATING ROLE OF PURCHASE INTENTION - Suastiari, Ni Kadek Sisi; Mahyuni, Luh Putu (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
This study aims to analyze the role of purchase intention in mediating the factors influencing e-commerce user satisfaction. The sample of this study was e-commerce users in Canggu Village, and 240 respondents were used. Data were collected by distributing questionnaires using Google Forms and were analyzed using SEM-PLS. The results show that effort expectancy and trust positively and significantly affect purchase intention. In contrast, performance expectancy and self-efficacy have a negative and insignificant effect. Effort expectancy, intention to purchase, self-efficacy, and trust positively and significantly affect e-commerce user satisfaction, whereas performance expectancy has a negative effect. Intention to purchase can positively and significantly mediate the effect of effort expectancy and trust on e-commerce user satisfaction but not on performance expectancy and self-efficacy. The results of this study indicate that to increase intention to purchase and e-commerce user satisfaction, several things need to be considered, including user trust must be maintained and ease of use must be considered so that users can feel satisfaction with the system.JEL : M21, M13, O33ABSTRAKPenelitian ini bertujuan untuk menganalisis peran intention to purchase dalam memediasi faktor-faktor yang mempengaruhi kepuasan pengguna e-commerce. Sampel dalam penelitian ini adalah pengguna e-commerce di Desa Canggu, sebanyak 240 responden. Data dikumpulkan melalui penyebaran kuesioner dengan menggunakan Google Forms dan . dianalisis dengan menggunakan SEM-PLS. Hasil riset menunjukkan bahwa effort expectancy dan trust berpengaruh positif dan signifikan terhadap intention to purchase, sementara performance expectancy dan self-efficacy berpengaruh negatif dan tidak signifikan. Effort expectancy, intention to purchase, self-efficacy, dan trust berpengaruh positif dan signifikan terhadap kepuasan pengguna e-commerce, sementara performance expectancy berpengaruh negatif. Intention to purchase mampu memediasi secara positif dan signifikan pengaruh effort expectancy dan trust terhadap kepuasan pengguna e-commerce, tetapi tidak untuk performance expectancy dan self-efficacy. Hasil penelitian ini menunjukkan bahwa untuk meningkatkan intention to purchase dan e-commerce user satisfaction, beberapa hal perlu diperhatikan, antara lain trust pengguna harus dijaga dan kemudahan penggunaan harus diperhatikan agar pengguna dapat merasakan satisfaction terhadap sistem.Kata   Kunci  : dimensi kepuasan, Intention to purchase, pengguna e-commerce.